An outcome evaluation of the success for kids program - Maestas, Nicole (Technical report (Rand Corporation), 2010)
This report presents results from a multisite, quantitative evaluation of the international Success for Kids (SFK) after-school program. The program seeks to build resilience in children by teaching them to access inner resources and build positive connections with others. The SFK program is unlike most after-school programs both in its focus on spiritual development and in its emphasis on outcomes related to resilience rather than academics. The authors found that the program had beneficial effects on adaptive skills, behavioral problems, overexternalization of problems, and school problems, and the effects persisted at 12-week follow-up. Interestingly, the program positively affected school-related outcomes, even though SFK is not an academic intervention. Specifically, it improved reported study skills and reduced reported learning problems and attention problems. Overall, a major strength of the program appears to be its careful attention to uniformity of program delivery -- in particular, its standardized curriculum, use of experienced teachers, and formal teacher-training program.